Antibacterial Zr-Nb alloy for hip joint, powder and laser additive manufacturing method
By defining the composition of Zr-Nb alloy and aerosol powdering technology, combining laser additive manufacturing and thermal isostatic pressure treatment, the wear resistance and antibacterial properties of hip materials are solved, and the hips with high yield strength and antibacterial effects are achieved Articular material preparation avoids segregation and cracks, and is suitable for high pressure and strong magnetic field environments.
Patent Information
- Application Number
- CN202411317618.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Existing hip prosthetic materials are prone to wear and bacterial infection at the friction interface, and it is difficult to achieve good wear resistance and antibacterial properties, especially the segregation and crack problems caused by mixing elements during the preparation process are difficult to solve.
By defining the composition of Zr-Nb alloy, using aerosol powder and laser additive manufacturing methods, Zr-Nb alloy powder with good wear resistance and antibacterial properties was prepared, and Cu was formed by hot isostatic pressure and deep cold treatment. -N antibacterial layer and Zr-O wear-resistant layer to ensure material uniformity and magnetic compatibility.
The high yield strength, good antibacterial effect and wear resistance of hip joint materials are achieved, segregation and crack problems are avoided, and the use needs under high pressure is met, and artifacts are avoided in the diagnosis of strong magnetic fields.
Smart Images

Figure CN119194165A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal materials, and specifically relates to an antibacterial Zr-Nb alloy, powder and laser additive manufacturing method for hip joints. Background Art
[0002] Total hip replacement has become the main method for treating severe femoral head necrosis in young and middle-aged patients due to its advantages of fast recovery, effective improvement of quality of life and few complications. The intensity and frequency of hip joint activities in young and middle-aged patients are much greater than those in the elderly, so higher requirements are placed on the service life of the prosthesis. Wear particles and bone dissolution caused by the friction interface of the prosthesis are important factors that affect the life of the prosthesis after hip replacement and ultimately lead to failure.
[0003] In the prior art, for example, the invention patent with announcement number CN112404431B discloses a zirconium-niobium alloy hip joint prosthesis system containing an oxide layer and a preparation method. By forming an oxide layer on the surface of the femoral head and the liner after oxidation, the friction interface has super wear resistance and low wear rate. However, in this scheme, it is difficult to control the thickness of the oxide layer. If the thickness is thin, the wear resistance is poor, while if the thickness is thick, cracks may form between the oxide layer and the matrix. PBR is used to characterize whether the metal oxide layer has a protective effect. When the PBR value is between 1 and 2.5, the oxide film formed by the metal oxide generally has a good protective effect. If the PBR value is too large, the volume expansion of the metal oxide causes stress in the surface film, causing cracks in the oxide film, which is not conducive to the growth of the oxide film. Secondly, artificial joints are often sensitive to bacterial adhesion and are more likely to cause bacterial infections. In order to give the material surface antibacterial properties, it is necessary to construct the antibacterial surface in a targeted manner according to the mechanism of bacterial infection, and give it antibacterial properties to reduce the adhesion and reproduction of bacteria, thereby avoiding the occurrence of infection; the invention patent with publication number CN102676985A uses glow ion diffusion technology to prepare an antibacterial copper diffusion layer on the surface of medical titanium alloy. Wu Haibo et al. used magnetron sputtering technology to sputter Ti-Cu thin film on the surface of medical pure titanium, combined with micro-arc oxidation and ion high-temperature nitridation technology, to prepare Cu-TiO 2 and Ti-Cu-N antibacterial coating, but this technical solution uses mixed titanium alloy powder and copper powder, and it is difficult to mix the two well even with a high-energy ball mill. Therefore, it is an urgent problem to prepare a Zr-Nb alloy with good wear resistance, antibacterial properties and suitable for aerosol powder making process. Summary of the invention
[0004] To solve the above problems, the present invention provides an antibacterial Zr-Nb alloy for hip joints, powder and laser additive manufacturing method. By limiting the composition of the Zr-Nb alloy, it is ensured that it is suitable for gas atomization powder making, avoiding segregation during the powder making process, resulting in poor tissue uniformity, and cracks under the action of external forces.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] The invention provides an antibacterial Zr-Nb alloy for hip joints. The Zr-Nb alloy is suitable for atomization powder making. The Zr-Nb alloy consists of Zr, Nb, Cu and inevitable impurities. By mass percentage, Nb: 25-30%, Cu: 8-10%.
[0007] Further, Nb: 28%, Cu: 8%.
[0008] The present invention also provides an antibacterial Zr-Nb alloy powder for hip joints, wherein the Zr-Nb alloy powder is obtained by powdering the Zr-Nb alloy in claim 1 or 2 through gas atomization.
[0009] The present invention also provides a method for preparing antibacterial Zr-Nb alloy powder for hip joints, comprising weighing Zr, Nb and Cu source materials according to mass percentage; smelting the Zr source material, Nb source material and Cu source material to prepare casting rods, using the casting rods as consumable electrodes and performing aerosolization powder making.
[0010] Furthermore, the Zr source material, the Nb source material and the Cu source material are Zr-Cu alloy, Nb-Cu alloy and Zr metal.
[0011] Furthermore, the Zr source material, the Nb source material and the Cu source material are vacuum melted, and after being completely melted, they are cast into cast rods, and the cast rods are turned over and remelted at least three times; the prepared cast rods are used as consumable electrodes, and the melt after the cast rods are melted is subjected to primary and secondary gas atomization in a vacuum environment; the primary gas atomization adopts an annular nozzle, the gas pressure is 2.9-3.0MPa, and the gas outlet convergence angle is 22-25°; the secondary gas atomization adopts an annular nozzle, the gas pressure is 1.8-2.2MPa, the gas outlet convergence angle is 32-35°, and the temperature range of the secondary gas atomization is 400-500°C; the initially prepared Zr-Nb alloy powder is sieved to obtain.
[0012] Furthermore, by sieving, Zr-Nb alloy powder with a particle size between 300-500 meshes is obtained.
[0013] The present invention also provides a method for preparing a hip joint using an antibacterial Zr-Nb alloy, wherein the hip joint is prepared by laser selective melting using the above-mentioned Zr-Nb alloy powder or the Zr-Nb alloy powder prepared by the above-mentioned preparation method; the method comprises the following steps: scanning a patient's hip joint by CT to obtain 3D data, and performing layered slicing on the model; importing the 3D data after the layered slicing into a laser 3D printing system, and performing 3D printing on the Zr-Nb alloy powder to precisely form a hip joint blank; performing hot isostatic pressing and deep cryogenic treatment on the prepared hip joint blank, machining, polishing, cleaning and drying the obtained product, and then placing it in a mixed gas of nitrogen and oxygen for nitriding and oxidation treatment to obtain the hip joint.
[0014] Furthermore, a body-centered cubic unit cell is used in the modeling process, and the porosity is controlled by controlling the diameter of the pillars constituting the body-centered cube.
[0015] Furthermore, the prepared hip joint is subjected to hot isostatic pressing and deep cryogenic treatment, including: hot isostatic pressing the prepared hip joint blank, the hot isostatic pressing process is: under an argon protective atmosphere, the temperature is raised to 1200-1300°C, maintained at a pressure of 120-160MPa for 6 hours, and cooled with the furnace; then the hip joint blank after hot isostatic pressing is cooled to -60--70°C at a rate of 2-4°C / min and kept warm for at least 2 hours, and then placed in liquid nitrogen and kept for at least 5 hours; in the nitrogen and oxygen mixed gas, the proportion of oxygen is 5-8%, the total flow rate is 60-80ml / min, the temperature is first raised to 200 degrees Celsius and maintained for 30-50 minutes, then the temperature is raised to 500-600°C and maintained for 5-6 hours, and then the temperature is lowered to 400-450°C and maintained for at least 10 hours.
[0016] The beneficial effects brought by the technical solution provided by the embodiment of the present invention include:
[0017] The Zr-Nb alloy for hip joint provided by the present invention needs to meet the following requirements: (1) It is suitable for preparing hip joints. Hip joints are subject to high pressure. Generally, the yield strength of the solid sample is required to be above 500 MPa, and the yield strength of the trabeculae is required to be above 15 MPa; (2) Cu in the alloy can form a Cu-N antibacterial layer. If the Cu content is low, the area of the formed Cu-N antibacterial layer is small, and an effective antibacterial effect cannot be achieved. Secondly, if the Cu-N antibacterial layer occupies a large area, the area occupied by the Zr-O layer is small, and the wear resistance of the prepared product is poor. Therefore, the present application strictly limits the ratio of Zr, Nb and Cu; (3) To meet the powder making requirements, 3D printing laser selection sintering is adopted, and the prepared powder needs to have a certain sphericity to facilitate subsequent printing. Secondly, the prepared material performance and composition are required to be uniform and have a high yield, and serious segregation, satellite powder and irregular powder and other problems should not occur; (4) Magnetic compatibility, avoiding the problem of artifacts caused by high magnetic susceptibility in strong magnetic field diagnosis in the prior art. The technical solution provided by the present invention contains only Zr, Nb and Cu elements, which avoids serious segregation caused by the addition of multiple elements. The prepared product has poor uniformity of mechanical properties. On the other hand, its content is controlled to meet the above requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 A body-centered cubic unit cell provided by an embodiment of the present invention;
[0020] Figure 2 This is an electron microscope image of the Zr-Nb alloy powder prepared in Example 1 of the present invention;
[0021] Figure 3 The morphology of the Zr-Nb alloy block prepared in Example 4 of the present invention with different reduction amounts;
[0022] Figure 4 This is a microstructure morphology diagram of a Zr-Nb alloy block prepared in Example 4 of the present invention;
[0023] Figure 5 This is an electron microscope image of the Zr-Nb alloy powder prepared in Comparative Example 1 of the present invention;
[0024] Figure 6 This is a morphology diagram of the Zr-Nb alloy block after fracturing prepared in Comparative Example 1 of the present invention;
[0025] Figure 7 The morphology of the Zr-Nb alloy block prepared in Comparative Example 1 of the present invention with different reduction amounts;
[0026] Figure 8 This is a microstructure morphology diagram of the Zr-Nb alloy block prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The specific implementation of the present invention is not limited to the specific embodiments given here, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the disclosed specific embodiments.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and do not limit the present invention.
[0029] The embodiment of the present invention provides an antibacterial Zr-Nb alloy for hip joints, which is suitable for aerosol powder making. It is characterized in that the Zr-Nb alloy consists of Zr, Nb, Cu and inevitable impurities, and in terms of mass percentage, Nb: 25-30%, Cu: 8-10%.
[0030] The Zr-Nb alloy for hip joint provided by the present invention needs to meet the following requirements: (1) It is suitable for preparing hip joints. Hip joints are subject to high pressure. Generally, the yield strength of the solid sample is required to be above 500 MPa, and the yield strength of the trabeculae is required to be above 15 MPa; (2) Cu in the alloy can form a Cu-N antibacterial layer. If the Cu content is low, the area of the formed Cu-N antibacterial layer is small, and an effective antibacterial effect cannot be achieved. Secondly, if the Cu-N antibacterial layer occupies a large area, the area occupied by the Zr-O layer is small, and the wear resistance of the prepared product is poor. Therefore, the present application strictly limits the ratio of Zr, Nb and Cu; (3) To meet the powder making requirements, 3D printing laser selection sintering is adopted, and the prepared powder needs to have a certain sphericity to facilitate subsequent printing. Secondly, the prepared material performance and composition are required to be uniform and have a high yield, and serious segregation, satellite powder and irregular powder and other problems should not occur; (4) Magnetic compatibility, avoiding the problem of artifacts caused by high magnetic susceptibility in strong magnetic field diagnosis in the prior art. The technical solution provided by the present invention contains only Zr, Nb and Cu elements, which avoids serious segregation caused by the addition of multiple elements. The prepared product has poor uniformity of mechanical properties. On the other hand, its content is controlled to meet the above requirements.
[0031] Preferably, Nb: 28%, Cu: 8%.
[0032] The embodiment of the present invention further provides an antibacterial Zr-Nb alloy powder, wherein the Zr-Nb alloy powder is obtained by powdering the above Zr-Nb alloy through gas atomization.
[0033] The embodiment of the present invention also provides a method for preparing the antibacterial Zr-Nb alloy powder for hip joint, comprising:
[0034] S10. Weigh Zr, Nb, and Cu source materials according to mass percentage.
[0035] It is understandable that the Zr, Nb, and Cu source materials are materials that provide sources of Zr, Nb, and Cu elements, and can be single metals or alloys. As preferred embodiments of the present invention, the Zr source material, the Nb source material, and the Cu source material are Zr-Cu alloy, Nb-Cu alloy, and Zr metal. In the batching process, the Nb-Cu alloy is preferred to meet the required amount of Nb and the required amount of copper, and the Zr-Cu alloy and Zr metal are considered secondly. Since the melting point of the Nb element is relatively high, reaching 2468°C, the Nb-Cu alloy can greatly reduce the melting temperature, avoiding the volatilization problem of the Cu or Zr element at high temperature during the smelting process.
[0036] S11: The Zr source material, the Nb source material and the Cu source material are melted to form a cast rod, and the cast rod is used as a consumable electrode and subjected to gas atomization powder making.
[0037] The Zr source material, Nb source material and Cu source material are vacuum melted, and cast into cast rods after being completely melted. The cast rods are turned over and remelted at least three times to improve the uniformity of element distribution in the prepared cast rods. Specifically, the vacuum environment is not more than 10Pa, and a medium frequency induction melting furnace is used for melting, the melting current is 100-110A, the melting time is 30-50min, and the materials are refined after being completely melted. After the refining is completed, they are poured into a mold to obtain alloy cast rods with a diameter of 50-60mm and a length of 50-100cm, which are used as consumable electrodes for subsequent gas atomization powder making.
[0038] The gas atomization powder making process is as follows: the prepared cast rod is used as a consumable electrode, and the melt after the cast rod is melted is subjected to primary gas atomization and secondary gas atomization in a vacuum environment; the primary gas atomization adopts an annular nozzle, the gas pressure is 2.9-3.0MPa, and the gas outlet convergence angle is 22-25°; the secondary gas atomization adopts an annular nozzle, the gas pressure is 1.8-2.2MPa, the gas outlet convergence angle is 32-35°, and the working range temperature range of the secondary gas atomization is 400-500°C; the primary gas atomization adopts an annular nozzle, the gas pressure is 1.8-2.2MPa, the gas outlet convergence angle is 32-35°, and the working range temperature range of the secondary gas atomization is 400-500°C; the secondary ... Gas atomization is used to crush the melt. After crushing, the droplets are spherical under the action of surface tension, but the liquid is prone to collision and adhesion at this time, resulting in poor sphericity of the powder. This application controls the content of Zr, Nb and Cu, combines secondary gas atomization, and sets the temperature range of the secondary gas atomization to 400-500°C. It can prepare qualified powders with a yield rate of up to 80%, and high sphericity. By testing a batch of fifty samples at ten different locations for statistics, the sphericity is as high as more than 90%. The main reason is that although the addition of the Cu element will cause segregation problems, it also brings corresponding advantages, that is, the synchronization of the droplet surface and internal solidification time increases, and the satellite powder can be effectively removed by secondary gas atomization without increasing the surface irregularity.
[0039] Specifically, the gas atomization powder making process of the present application is: under a vacuum degree not greater than 0.01Pa, an inert gas is sprayed through an annular nozzle to crush the metal melt, and the airflow pressure is 10-12Mpa. The inert gas in the primary gas atomization is preferably argon containing 1% nitrogen by volume, and the secondary gas atomization is preferably pure argon. Due to the high difficulty of nitriding the alloy, a small amount of nitrogen is added during the gas atomization powder making process to nitride the powder to a certain extent. Due to the limitation of the elements in the present application, subsequent nitrides are easily accumulated on the surface of the prepared product.
[0040] S12 is to sieve the preliminarily prepared Zr-Nb alloy powder. Specifically, by sieving, a Zr-Nb alloy powder with a particle size between 300-500 meshes is obtained.
[0041] The embodiment of the present invention also provides a method for preparing a hip joint with an antibacterial Zr-Nb alloy, using the above Zr-Nb alloy powder, comprising the following steps:
[0042] S20 obtains 3D data by CT scanning the patient's hip joint and performs layered slice processing on the model.
[0043] The body-centered cubic unit cell is used in the modeling process, which consists of four diagonal pillars, such as Figure 1As shown in the figure, the porosity is controlled by controlling the diameter of the pillars that make up the body-centered cubic. In order to ensure the printing accuracy and control the defects in the printing process, the minimum system diameter is limited to 400μm and the pillar length is within 2mm. Within the above range, the areas with different porosities can be well connected without stress concentration.
[0044] S21 imports the 3D data after layered slicing into the laser 3D printing system, and 3D prints the Zr-Nb alloy powder to precisely form the hip joint blank.
[0045] Specifically, in the 3D printing system, the laser forming process parameters are: laser power is 120-150W, scanning speed is 150-180mm / s, scanning spacing is 50-60μm, laser spot is 60-70μm, and powder thickness is 10-40μm.
[0046] S22 performs hot isostatic pressing and deep cryogenic treatment on the prepared hip joint blank.
[0047] Specifically, it includes: subjecting the prepared hip joint blank to hot isostatic pressing treatment, the hot isostatic pressing process is: under an argon protective atmosphere, heating to 1200-1300°C, maintaining at a pressure of 120-160MPa for 6 hours, and cooling with the furnace; then reducing the temperature of the hip joint blank after hot isostatic pressing to -60--70°C at a rate of 2-4°C / min and keeping it for at least 2 hours, and then placing it in liquid nitrogen and maintaining it for at least 5 hours.
[0048] S23: machining, polishing, cleaning and drying the obtained product, and then placing it in a mixed gas of nitrogen and oxygen for nitriding and oxidation treatment to obtain the hip joint.
[0049] In the nitrogen and oxygen mixed gas, the proportion of oxygen is 5-8%, the total flow rate is 60-80ml / min, first heat up to 200 degrees Celsius and keep for 30-50 minutes, then heat up to 500-600℃ and keep for 5-6 hours, then cool down to 400-450℃ and keep for at least 10 hours.
[0050] It should be pointed out that the wear-resistant layer in the present application is mainly realized by Zr-O, and the antibacterial layer is mainly realized by Cu-N / Cu-O. Through step-by-step insulation, at a temperature of 200°C, an oxide layer is mainly generated. When the temperature rises to 500-600°C, the generation of nitrides increases to improve the generation of the Cu-N antibacterial layer. Secondly, since the wear-resistant layer and the antibacterial layer of the present application are mixed and distributed on the substrate, there is an internal stress problem. Therefore, the interface of oxides or nitrides of different properties is annealed and coordinated at a temperature of 400-500°C to avoid stress concentration and film cracking. By measuring different areas, the surface of the wear-resistant layer with antibacterial effect prepared by the present application, the proportion of Cu-N film is 7-8%, which can effectively carry out antibacterial, and the proportion of Cu-O film does not exceed 2%, and the rest is mainly Zr-O. Secondly, the addition of the Cu-N layer in the present invention can be coordinated with the Zr-O layer, and the requirements for the thickness of the Zr-O layer are passivated.
[0051] Characterization method:
[0052] 1) Magnetic susceptibility, the magnetic susceptibility measurement method refers to GB / Z 26082-2010 "Nanomaterial DC susceptibility (magnetic moment) measurement method", which is as follows: 4*4*2mm square samples are cut from the ingot by wire cutting, the surface oxide scale is polished clean with metallographic sandpaper, and then placed in a vibrating magnetometer (VSM), the magnetic field intensity is 3T, and the magnetic field direction is perpendicular to the 4*4mm plane. The obtained data are linearly fitted using origin software, and the slope of the straight line is the mass magnetic susceptibility (χm), which is then converted into volume magnetic susceptibility (χv), and the formula is χv=χm×ρ×4π, (ρ is the alloy density, π is the pi).
[0053] 2) Elastic modulus. The measurement method of elastic modulus refers to GB / T 8653-2007 "Test method for elastic modulus, chord modulus and tangent modulus of metallic materials". The specific measurement method is as follows: cut blocks of specific size from the ingot by wire cutting, carry out corresponding heat treatment process, and then further process by wire cutting to obtain tensile specimens. Use a universal tensile testing machine equipped with an optical extensometer to carry out tensile test, obtain stress-strain curve, perform linear fitting on it, and obtain the corresponding elastic modulus.
[0054] 3) Yield strength: According to GB / T 7314-2017 standard, the compressive properties of metal materials at room temperature are measured.
[0055] 4) Antibacterial test: Staphylococcus aureus was selected as the test object, and the antibacterial properties of artificial hip joints were tested in accordance with QB / T2591-2003 "Antibacterial Plastics - Antibacterial Performance Test Methods and Antibacterial Effects". The results showed that after one day of the test, the antibacterial rate of titanium alloy hip joints against Staphylococcus aureus reached 99%, and after 4 days of the test, the antibacterial rate still reached 98%, showing good long-lasting antibacterial properties.
[0056] 5) Wear detection: The microhardness of the femoral stem of the embodiment was measured using a microhardness tester (MHVS-1000PLUS, Shanghai Aolong Xingdi Testing Equipment Co., Ltd., China). The test load was 0.05 kg, the specimen loading time was 25 s, and 8 points were taken for each specimen to calculate its average hardness.
[0057] 6) The bonding strength between the membrane and the substrate was determined by applying 2% strain to the hip joint, repeating the experiment 100,000 times, and observing the state of the membrane.
[0058] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0059] Example 1
[0060] The embodiment of the present invention provides a method for preparing antibacterial Zr-Nb alloy powder for hip joint, comprising:
[0061] S10 Weigh the Zr, Nb and Cu source materials according to mass percentage.
[0062] Weigh Zr, Nb, and Cu source materials according to Nb: 28%, Cu: 8%, and Zr: 64%.
[0063] S11: The Zr source material, the Nb source material and the Cu source material are melted to form a cast rod, and the cast rod is used as a consumable electrode and subjected to gas atomization powder making.
[0064] The Zr source material, the Nb source material and the Cu source material are vacuum melted and cast into cast rods after being completely melted. The cast rods are turned over and remelted three times to improve the uniformity of element distribution in the prepared cast rods.
[0065] The atomization powder making process is as follows: the prepared cast rod is used as a consumable electrode, and the melt after the cast rod is melted is subjected to primary atomization and secondary atomization in a vacuum environment; the primary atomization adopts an annular nozzle, the gas pressure is 2.9MPa, and the gas outlet convergence angle is 22°; the secondary atomization adopts an annular nozzle, the gas pressure is 1.8MPa, and the gas outlet convergence angle is 32°, and the temperature range of the secondary atomization action interval is 400°C.
[0066] S12: Screening the preliminarily prepared Zr-Nb alloy powder to obtain Zr-Nb alloy powder with a particle size between 300-500 meshes.
[0067] The prepared Zr-Nb alloy powder is Figure 2 As shown, it can be seen that the powder has good sphericity and few satellite powders.
[0068] Example 2
[0069] The embodiment of the present invention provides a method for preparing antibacterial Zr-Nb alloy powder for hip joint, comprising:
[0070] S10 Weigh the Zr, Nb and Cu source materials according to mass percentage.
[0071] Weigh Zr, Nb and Cu source materials according to Nb: 25%, Cu: 5%, and Zr: 70%.
[0072] S11: The Zr source material, the Nb source material and the Cu source material are melted to form a cast rod, and the cast rod is used as a consumable electrode and subjected to gas atomization powder making.
[0073] The Zr source material, the Nb source material and the Cu source material are vacuum melted and cast into cast rods after being completely melted. The cast rods are turned over and remelted three times to improve the uniformity of element distribution in the prepared cast rods.
[0074] The atomization powder making process is as follows: the prepared cast rod is used as a consumable electrode, and the melt after the cast rod is melted is subjected to primary and secondary atomization in a vacuum environment; the primary atomization adopts an annular nozzle, the gas pressure is 2.9MPa, and the gas outlet convergence angle is 23°; the secondary atomization adopts an annular nozzle, the gas pressure is 2MPa, and the gas outlet convergence angle is 34°, and the temperature range of the secondary atomization action interval is 450°C.
[0075] S12: Screening the preliminarily prepared Zr-Nb alloy powder to obtain Zr-Nb alloy powder with a particle size between 300-500 meshes.
[0076] The prepared Zr-Nb alloy powder has good sphericity and less satellite powder.
[0077] Example 3
[0078] The embodiment of the present invention provides a method for preparing antibacterial Zr-Nb alloy powder for hip joint, comprising:
[0079] S10 Weigh the Zr, Nb and Cu source materials according to mass percentage.
[0080] Weigh Zr, Nb and Cu source materials according to Nb: 30%, Cu: 10% and Zr: 60%.
[0081] S11: The Zr source material, the Nb source material and the Cu source material are melted to form a cast rod, and the cast rod is used as a consumable electrode and subjected to gas atomization powder making.
[0082] The Zr source material, the Nb source material and the Cu source material are vacuum melted and cast into cast rods after being completely melted. The cast rods are turned over and remelted three times to improve the uniformity of element distribution in the prepared cast rods.
[0083] The aerosol powder making process is as follows: the prepared cast rod is used as a consumable electrode, and the melt after the cast rod is melted is subjected to primary atomization and secondary atomization in a vacuum environment; the primary atomization adopts an annular nozzle, the gas pressure is 3.0MPa, and the gas outlet convergence angle is 25°; the secondary atomization adopts an annular nozzle, the gas pressure is 2.2MPa, and the gas outlet convergence angle is 35°, and the temperature range of the secondary atomization action interval is 500°C.
[0084] S12: Screening the preliminarily prepared Zr-Nb alloy powder to obtain Zr-Nb alloy powder with a particle size between 300-500 meshes.
[0085] The prepared Zr-Nb alloy powder has good sphericity and less satellite powder.
[0086] Example 4
[0087] The embodiment of the present invention provides a method for preparing a hip joint using an antibacterial Zr-Nb alloy, using the Zr-Nb alloy powder prepared in Example 1, comprising:
[0088] S20 obtains 3D data by CT scanning the patient's hip joint and performs layered slice processing on the model.
[0089] S21 imports the 3D data after layered slicing into the laser 3D printing system, and 3D prints the Zr-Nb alloy powder to precisely form the hip joint blank; at the same time, in order to characterize the performance of the material, the same process is used to prepare the metal block.
[0090] S22 performs hot isostatic pressing and deep cryogenic treatment on the prepared hip joint blank.
[0091] Specifically, it includes: subjecting the prepared hip joint blank to hot isostatic pressing treatment, the hot isostatic pressing process is: under an argon protective atmosphere, heating to 1200°C, maintaining at a pressure of 120MPa for 6 hours, and cooling with the furnace; then reducing the temperature of the hip joint blank after hot isostatic pressing to -60°C at a rate of 2°C / min and keeping it for 2 hours, and then placing it in liquid nitrogen and maintaining it for 5 hours.
[0092] S23: machining, polishing, cleaning and drying the obtained product, and then placing it in a mixed gas of nitrogen and oxygen for nitriding and oxidation treatment to obtain the hip joint.
[0093] In the nitrogen and oxygen mixed gas, the proportion of oxygen is 5%, the total flow rate is 60ml / min, the temperature is first raised to 200 degrees Celsius and maintained for 30 minutes, then raised to 500℃ and maintained for 5 hours, and then cooled to 400℃ and maintained for 10 hours.
[0094] The elastic modulus and yield strength of metal blocks are measured, such as Figure 3 As shown in the figure, it can be seen that the block will not produce cracks after compression, and from Figure 4 It can be seen that the prepared product has less segregation and impurities and uniform performance. The magnetic susceptibility, antibacterial properties, membrane state and hardness of the prepared hip joint were tested, and the results are shown in Table 1.
[0095] Example 5
[0096] The embodiment of the present invention provides a method for preparing a hip joint using an antibacterial Zr-Nb alloy, using the Zr-Nb alloy powder prepared in Example 1, comprising:
[0097] S20 obtains 3D data by CT scanning the patient's hip joint and performs layered slice processing on the model.
[0098] S21 imports the 3D data after layered slicing into the laser 3D printing system, and 3D prints the Zr-Nb alloy powder to precisely form the hip joint blank.
[0099] S22 performs hot isostatic pressing and deep cryogenic treatment on the prepared hip joint blank.
[0100] Specifically, it includes: subjecting the prepared hip joint blank to hot isostatic pressing treatment, the hot isostatic pressing process is: under an argon protective atmosphere, heating to 1250°C, maintaining at a pressure of 140MPa for 6 hours, and cooling with the furnace; then reducing the temperature of the hip joint blank after hot isostatic pressing to -65°C at a rate of 3°C / min and keeping it for 2 hours, and then placing it in liquid nitrogen and maintaining it for 5 hours.
[0101] S23: machining, polishing, cleaning and drying the obtained product, and then placing it in a mixed gas of nitrogen and oxygen for nitriding and oxidation treatment to obtain the hip joint.
[0102] In the nitrogen and oxygen mixed gas, the proportion of oxygen is 7%, the total flow rate is 70ml / min, the temperature is first raised to 200 degrees Celsius and maintained for 40 minutes, then raised to 550℃ and maintained for 6 hours, and then cooled to 450℃ and maintained for 10 hours.
[0103] The elastic modulus and yield strength of the metal block were measured, and the magnetic susceptibility, antibacterial properties, membrane state and hardness of the prepared hip joint were tested. The results are shown in Table 1.
[0104] Example 6
[0105] The embodiment of the present invention provides a method for preparing a hip joint using an antibacterial Zr-Nb alloy, using the Zr-Nb alloy powder prepared in Example 1, comprising:
[0106] S20 obtains 3D data by CT scanning the patient's hip joint and performs layered slice processing on the model.
[0107] S21 imports the 3D data after layered slicing into the laser 3D printing system, and 3D prints the Zr-Nb alloy powder to precisely form the hip joint blank.
[0108] S22 performs hot isostatic pressing and deep cryogenic treatment on the prepared hip joint blank.
[0109] Specifically, it includes: subjecting the prepared hip joint blank to hot isostatic pressing treatment, the hot isostatic pressing process is: under an argon protective atmosphere, heating to 1300°C, maintaining at a pressure of 160MPa for 6 hours, and cooling with the furnace; then reducing the temperature of the hip joint blank after hot isostatic pressing to -70°C at a rate of 4°C / min and keeping it for 2 hours, and then placing it in liquid nitrogen and maintaining it for 5 hours.
[0110] S23: machining, polishing, cleaning and drying the obtained product, and then placing it in a mixed gas of nitrogen and oxygen for nitriding and oxidation treatment to obtain the hip joint.
[0111] In the nitrogen and oxygen mixed gas, the proportion of oxygen is 8%, the total flow rate is 80ml / min, the temperature is first raised to 200 degrees Celsius and maintained for 50 minutes, then raised to 600℃ and maintained for 6 hours, and then cooled to 450℃ and maintained for at least 10 hours.
[0112] The elastic modulus and yield strength of the metal block were measured, and the magnetic susceptibility, antibacterial properties, membrane state and hardness of the prepared hip joint were tested. The results are shown in Table 1.
[0113] Comparative Example 1
[0114] Different from Example 4, the Cu content in the Zr-Nb alloy used in this comparative example is 5%.
[0115] The prepared Zr-Nb alloy powder is Figure 5 As shown, there are more satellite powders and the sphericity is poor. The prepared block is compressed, as shown in Figure 6 and 7 As shown, the block is fractured; Figure 8 It can be concluded that when the Cu content decreases, the quality of the alloy powder is worse, the printing effect is not good, and the prepared product contains more impurities. The elastic modulus and yield strength of the metal block were measured, and the magnetic susceptibility, antibacterial properties, film state and hardness of the prepared hip joint were tested. The results are shown in Table 1.
[0116] Comparative Example 2
[0117] Different from Example 4, the Cu content in the Zr-Ni alloy used in this comparative example is 12.
[0118] The prepared Zr-Nb alloy powder has more satellite powder and poor sphericity. The prepared block is compressed and fractured, the elastic modulus and yield strength of the metal block are measured, and the magnetic susceptibility, antibacterial properties, membrane state and hardness of the prepared hip joint are tested. The results are shown in Table 1.
[0119] Comparative Example 3
[0120] Different from Example 4, in the step S11 of preparing Zr—Nb alloy powder, only one atomization is used in this comparative example.
[0121] The elastic modulus and yield strength of the metal block were measured, and the results are shown in Table 1 The prepared hip joint was cracked.
[0122] Comparative Example 4
[0123] Different from Example 4, in the hip joint preparation process of this comparative example, the proportion of oxygen in the nitrogen and oxygen mixed gas is 4.
[0124] The elastic modulus and compressive strength of the metal block were measured, and the magnetic susceptibility, antibacterial properties, membrane state and hardness of the prepared hip joint were tested. The results are shown in Table 1.
[0125] Comparative Example 5
[0126] Different from Example 4, in the hip joint preparation process of this comparative example, the proportion of oxygen in the nitrogen and oxygen mixed gas is 10%.
[0127] The elastic modulus and yield strength of the metal block were measured, and the magnetic susceptibility, antibacterial properties, membrane state and hardness of the prepared hip joint were tested. The results are shown in Table 1.
[0128] Comparative Example 6
[0129] Different from Example 4, in the hip joint preparation process of this comparative example, the temperature is not raised to 500° C. and maintained for 5 hours, and then cooled to 400° C. and maintained for 10 hours.
[0130] The elastic modulus and yield strength of the metal block were measured, and the magnetic susceptibility, antibacterial properties, membrane state and hardness of the prepared hip joint were tested. The results are shown in Table 1.
[0131] Table 1 Performance test results of various embodiments and comparative examples
[0132]
[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An antibacterial Zr-Nb alloy for hip joint, the Zr-Nb alloy is suitable for aerosol powder making, characterized in that: The Zr-Nb alloy consists of Zr, Nb, Cu and inevitable impurities, wherein by mass percentage, Nb accounts for 25-30% and Cu accounts for 8-10%.
2. The Zr-Nb alloy according to claim 1, characterized in that Nb: 28%, Cu: 8%.
3. An antibacterial Zr-Nb alloy powder for hip joint, characterized in that: The Zr-Nb alloy powder is obtained by powdering the Zr-Nb alloy according to claim 1 or 2 by gas atomization.
4. A method for preparing antibacterial Zr-Nb alloy powder for hip joint as claimed in claim 3, characterized in that: Weigh Zr, Nb, and Cu source materials according to mass percentage; The Zr source material, the Nb source material and the Cu source material are melted to prepare a cast rod, and the cast rod is used as a consumable electrode and subjected to gas atomization powder making.
5. The preparation method according to claim 4, characterized in that: The Zr source material, the Nb source material and the Cu source material are Zr-Cu alloy, Nb-Cu alloy and Zr metal.
6. The preparation method according to claim 5, characterized in that: The Zr source material, the Nb source material and the Cu source material are vacuum melted and cast into cast rods after being completely melted, and the cast rods are turned over and remelted at least three times; The prepared cast rod is used as a consumable electrode, and the melt after the cast rod is melted is subjected to primary gas atomization and secondary gas atomization in a vacuum environment; The primary gas atomization adopts an annular nozzle, the gas pressure is 2.9-3.0MPa, and the gas outlet convergence angle is 22-25°; The secondary gas atomization adopts an annular nozzle, the gas pressure is 1.8-2.2MPa, the gas outlet convergence angle is 32-35°, and the temperature range of the secondary gas atomization is 400-500°C; The Zr-Nb alloy powder prepared preliminarily is obtained by sieving.
7. The preparation method according to claim 6, characterized in that: By sieving, Zr-Nb alloy powder with a particle size between 300-500 meshes is obtained.
8. A method for preparing a hip joint using an antibacterial Zr-Nb alloy, characterized in that: The hip joint is prepared by laser selective melting using the Zr-Nb alloy powder described in claim 3 or the Zr-Nb alloy powder prepared by the preparation method described in any one of claims 4 to 7; The steps include: The patient's hip joint is scanned by CT to obtain 3D data, and the model is sliced and processed; The 3D data after layered slicing is imported into the laser 3D printing system, and the Zr-Nb alloy powder is 3D printed to precisely form the hip joint blank; The prepared hip joint blank is subjected to hot isostatic pressing and deep cryogenic treatment. The obtained product is machined, polished, cleaned and dried, and then placed in a mixed gas of nitrogen and oxygen for nitridation and oxidation treatment to obtain the hip joint.
9. The method according to claim 8, characterized in that A body-centered cubic unit cell is used in the modeling process, and the porosity is controlled by controlling the diameter of the pillars that constitute the body-centered cube.
10. The method according to claim 9, characterized in that The prepared hip joint is subjected to hot isostatic pressing and deep cryogenic treatment, including: hot isostatic pressing the prepared hip joint blank, the hot isostatic pressing process is: in an argon protective atmosphere, heating to 1200-1300° C., maintaining at a pressure of 120-160 MPa for 6 hours, and cooling with the furnace; then cooling the hip joint blank after hot isostatic pressing to -60--70° C. at a rate of 2-4° C. / min and maintaining for at least 2 hours, and then placing in liquid nitrogen and maintaining for at least 5 hours; In the nitrogen and oxygen mixed gas, the proportion of oxygen is 5-8%, the total flow rate is 60-80ml / min, first heat up to 200 degrees Celsius and keep for 30-50 minutes, then heat up to 500-600℃ and keep for 5-6 hours, then cool down to 400-450℃ and keep for at least 10 hours.
Citation Information
Patent Citations
High-strength low-modulus biomedical zirconium alloy and preparation method thereof
CN116103539A
Magnetically compatible beta-type biomedical zirconium alloy as well as preparation method and application thereof
CN117965957A
Ti-zr sintered alloy
JP1985224727A
Metal composite, a biocompatible implant thereof and methods of fabricating thereof
US20190105876A1
Dispersion strengthened cobalt-chromium-molybdenum alloy produced by gas atomization
US4668290A
